The medical library association guide to data management for librarians /c edited by Lisa Federer - Federer, Lisa (Medical Library Association books, 2016)
The Medical Library Association Guide to Data Management for Librarians highlights the many ways that librarians are addressing researchers' changing needs at a variety of institutions. From foundations to applications, this book provides context for librarians who are new to it as well as new ideas and approaches for experienced data librarians